2004
DOI: 10.1103/physrevb.70.205318
|View full text |Cite
|
Sign up to set email alerts
|

Exchange energy tuned by asymmetry in artificial molecules

Abstract: Laterally coupled asymmetric quantum dots occupied by two electrons are studied using the exact diagonalization approach. It is shown that the asymmetry enhances the exchange energy, i.e., the triplet-singlet energy difference for finite magnetic fields. At high magnetic field, electrons enter the deepest dot more easily if they have parallel spins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 23 publications
2
98
0
Order By: Relevance
“…11 Our study 12 on electron systems in a single circular dot performed with a similar technique showed that the superposition of Gaussians very well approximates the angular momentum eigenstates. …”
Section: Double Dot Model and Methods Of Calculationsmentioning
confidence: 99%
“…11 Our study 12 on electron systems in a single circular dot performed with a similar technique showed that the superposition of Gaussians very well approximates the angular momentum eigenstates. …”
Section: Double Dot Model and Methods Of Calculationsmentioning
confidence: 99%
“…12,13,18,[26][27][28][29][30][31][32][33] Magnetizations in QDs have been measured indirectly with transport measurements 34 and recently with a direct technique with improved sensitivity. 35 For both measurements, semiclassical approaches cannot explain the results.…”
Section: Introductionmentioning
confidence: 99%
“…While extensive theoretical work focuses on the dependence of J on the system paramenters such as the inter-dot separation, the tunneling barrier between the QDs, and the external magnetic field, 2,3,4,5 the charge stability diagram of coupled QDs 6 has been studied to a lesser extent. Meanwhile, recent advances in experimental techniques have made it possible to study coupled QDs in the few-electron regime when each QD contains only one conduction electron (see, e.g., Refs.…”
mentioning
confidence: 99%